(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is the most important lever for social, economic and political transformation. A well educated population, equipped with the relevant knowledge, attitudes and skills is essential for economic and social development in the twenty first century. Education is the most potent tool for socio economic mobility and a key instrument for building an equitable and just society. Sarva Shiksha Abhiyan (SSA) is one of India’s major flagship programs for Universalisation of elementary education launched in 2000-2001. Universalisation of elementary education in India implies Universal access and enrolment, universal retention, bridging gender and social category gap in primary and upper primary education and elementary education of satisfactory quality.